1998
DOI: 10.1128/mcb.18.4.2262
|View full text |Cite
|
Sign up to set email alerts
|

The Microsatellite Sequence (CT)n · (GA)nPromotes Stable Chromosomal Integration of Large Tandem Arrays of Functional Human U2 Small Nuclear RNA Genes

Abstract: The multigene family encoding human U2 small nuclear RNA (snRNA) is organized as a single large tandem array containing 5 to 25 copies of a 6.1-kb repeat unit (the RNU2 locus). Remarkably, each of the repeat units within an individual U2 tandem array appears to be identical except for an irregular dinucleotide tract, known as the CT microsatellite, which exhibits minor length and sequence polymorphism. Using a somatic cell genetic assay, we previously noticed that the CT microsatellite appeared to stabilize ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…A number of authors have suggested another function for microsatellites and show that di-nucleotide repeats can act as recombination hot spots (Treco and Arnheim, 1986;Wahls et al, 1990;Bailey et al, 1998). This microsatellite function allows populations to recover genetic variation lost through genetic drift and rapidly adjust to evolutionary demands (Foster and Trimarchi, 1994;Rosenberg et al, 1994).…”
Section: Functional Importance Of Microsatellitesmentioning
confidence: 99%
“…A number of authors have suggested another function for microsatellites and show that di-nucleotide repeats can act as recombination hot spots (Treco and Arnheim, 1986;Wahls et al, 1990;Bailey et al, 1998). This microsatellite function allows populations to recover genetic variation lost through genetic drift and rapidly adjust to evolutionary demands (Foster and Trimarchi, 1994;Rosenberg et al, 1994).…”
Section: Functional Importance Of Microsatellitesmentioning
confidence: 99%
“…The 45-kb U1 repeats are slightly heterogeneous, but the 6.1-kb U2 repeat units are homogeneous except for a hypervariable CT dinucleotide repeat region (Fig. 1A) which may play a role in the stability (4) and/or concerted evolution of the array (54,57). Although U2 arrays differ in gene copy number from individual to individual, the arrays are stably inherited (55) and subject to dosage compensation (3,68).…”
mentioning
confidence: 99%
“…A study in humans has demonstrated that the microsatellite (CT)n stabilizes a long series of tandem integration of the transcription of the U2 snRNA genes (Bailey et al 1998). Thus, it is suggested that the function of these repeating units in multigene families is to conserve the tandem array (Liao and Weiner 1995).…”
Section: Discussionmentioning
confidence: 98%